THE USE OF THE UNCONSTITUTIONAL STATE OF AFFAIRS IN BRAZIL: CONTRIBUTIONS TO ESTABLISH APPLICATION CRITERIA - Casimiro Gomes Serafim, Matheus; Cysne Augusto Maia, Isabelly; Braga Albuquerque, Felipe (Revista da Faculdade de Direito do Sul de Minas, 2022)
Despite the reference to the Unconstitutional State of Affairs (USoA) in the trial of the precautionary measure of ADPF nº 347, the Supreme Federal Court of Brazil did not clarify which criteria should guide its application. Consequently, some problems may arise, such as its weakening, due to the possible indiscriminate use; lack of internal and external coherence in judicial decisions, since there are no uniform criteria of applicability, there is a risk that each magistrate will understand this practice of different way; and legal uncertainty, of not knowing precisely when the USoA may or may not be used. Thus, the purpose of this paper is to present the importance and the difficulties of establishing objective criteria for the use of USoA in future structural litigation. Furthermore, in order to contribute to the minimization of the identified problem, some initial criteria for the use of USoA are proposed, such as the exceptionality of the problem faced and the severity of the structural violation.